Research and analysis of resonant and stiffness of cylindrical dielectric elastomer actuator. (23rd June 2021) - Li, Jin; Sun, Lijie; Nguyen, Tuan Dung; Zhong, Tianyi; Liao, Xingyu
Abstract: Dielectric elastomer actuators draw great interest in the emerging technology of soft actuations. The drifting of resonance frequency and variable stiffness are commonly existed in soft actuations. This work studied the dynamic performances of a cylindrical dielectric elastomer actuator with coupled loads of tensile forces and variable voltages. The equation of motion for the axial are derived from Euler–Lagrange equation and are reduced into linear ordinary differential equations by the weighted average equivalent linearization method. It is found that the resonant frequency as well as the dynamic behavior can be tuned by variable electrical stimulus on the actuator. An analytical solution of the resonant frequency and equivalent stiffness have been derived in this paper, and have been verified by numerical simulations and experimental measurements. By changing the excitation voltages, the stiffness can be tuned as variable and controllable, which paves the way for future applications of the DE actuators with better performances and resilience.